PENGARUH PENGUATAN PENDIDIKAN KARAKTER (PPK) TERHADAP PERILAKU BULLYING DI SDI LIANG WAKAL - Oliva Yuliastri; Marselinus Robe (Program Studi Guru Sekolah Dasar (UNIKA Santu Paulus Ruteng), 2022)
This research analyzes the implementation of character education values ​​in schools to overcome student bullying. The results prove that bullying behavior still occurs. This has an impact on victims who experience trauma. The need for approaches and understanding the theory of elementary school student development that focuses on children's character education as a solution in overcoming student bullying behavior. However, the reality was that the implementation of character education was not supported by school programs, the facilities and abilities of teachers to achieve good character among students. So that character strengthening needs to be developed with the aim of being an initial guide for students in facing the challenges of life's journey. This research was a quantitative research , research design was simple correlation. The sample of students in grades 4 to 6, amounting to 40 students. The sampling technique used was purposive sampling where the sampling was based on considerations that focused on a particular goal on the grounds that the selected sample students were considered to be able to provide information and understand the contents of each questionnaire statement. The data analysis technique used in this research is a simple linear regression technique and descriptive statistics. The results of this research indicate that (1). There was no effect between PPK and bullying behavior at SDI Liang Wakal. This can be seen from the results of the simple regression analysis that was carried out, it was obtained that the calculated F was -0.253 and the test of the significance or significance of the regression coefficient obtained the value of Sig = 0.132 > 0.05. A negative coefficient (F_count) indicated that the character program and bullying behavior did not affect each other.